Aktivitas Antioksidan Klika Awar-awar (Ficus septica Burm. F) Asal Tanah Buton Selatan dengan Metode ABTS - Alim, Nur; Fauziah Noer, Sitti; Daniati, Wa (Jurnal Novem Medika Farmasi, 2023)
Phytochemical screening of the ethanol extract of Awar-awar bark was found to contain alkaloids, saponins, flavonoids, and polyphenols which have the potential as antioxidants, so a study was conducted on the antioxidant activity of the ethanol extract of awar-awar bark using the ABTS method. The purpose of this study was to determine the antioxidant activity of the ethanol extract awar-awar (Ficus septica Burm. F) bark from the Tanah Buton Selatan district using the ABTS method. The research method included extraction by maceration using 96% ethanol and testing the antioxidant activity with the ABTS method using a UV-Vis spectrophotometer at a maximum wavelength of 751 nm with the ascorbic acid standard. The results showed that the antioxidant activity of the ethanol extract of awar-awar bark obtained an IC50 value of 127.49 ± 2.53 μg/mL while ascorbic acid with an IC50 value of 2.6786 ± 0.312 μg/mL. The conclusions from the study showed that Awar-awar bark potential to a natural antioxidant